Estimating 10-year risk of lung and breast cancer by occupation in Switzerland - van der Linden, Bernadette Wilhelmina Antonia; Bovio, Nicolas; Arveux, Patrick; Bergeron, Yvan; Bulliard, Jean-Luc; Fournier, Evelyne; Germann, Simon; Konzelmann, Isabelle; Maspoli, Manuela; Rapiti, Elisabetta; Chiolero, Arnaud; Guseva Canu, Irina (Frontiers in Public Health, 2023)
Introduction Lung and breast cancer are important in the working-age population both in terms of incidence and costs. The study aims were to estimate the 10-year risk of lung and breast cancer by occupation and smoking status and to create easy to use age-, and sex-specific 10-year risk charts. Methods New lung and breast cancer cases between 2010 and 2014 from all 5 cancer registries of Western Switzerland, matched with the Swiss National Cohort were used. The 10-year risks of lung and breast cancer by occupational category were estimated. For lung cancer, estimates were additionally stratified by smoking status using data on smoking prevalence from the 2007 Swiss Health Survey. Results The risks of lung and breast cancer increased with age and were the highest for current smokers. Men in elementary professions had a higher 10-year risk of developing lung cancer compared to men in intermediate and managerial professions. Women in intermediate professions had a higher 10-year risk of developing lung cancer compared to elementary and managerial professions. However, women in managerial professions had the highest risk of developing breast cancer. Discussion The 10-year risk of lung and breast cancer differs substantially between occupational categories. Smoking creates greater changes in 10-year risk than occupation for both sexes. The 10-year risk is interesting for both patients and professionals to inform choices related to cancer risk, such as screening and health behaviors. The risk charts can also be used as public health indicators and to inform policies to protect workers.